2016
DOI: 10.1111/iep.12173
|View full text |Cite
|
Sign up to set email alerts
|

A 12‐month follow‐up study on the preventive effect of oral lansoprazole on acute exacerbation of chronic obstructive pulmonary disease

Abstract: The objective of this study was to evaluate the preventive effects of oral administration of lansoprazole on acute exacerbation of chronic obstructive pulmonary disease (COPD). Patients with COPD in groups C and D in the stable phase were stratified into a group with neither gastroesophageal reflux nor lansoprazole therapy (group A) and a group subjected to oral lansoprazole therapy (group B1 ) and a group not subjected to oral lansoprazole therapy (group B2 ). The frequency scale for the symptoms of gastroeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The significant decline in lung function with PPI and/or H 2 blocker use in this cohort is also likely due to confounding-by-indication. Xiong et al suggested that treatment of GERD with PPI in patients with COPD is associated with delayed deterioration of FEV 1 after 1-year follow-up [ 43 ]. However, several other studies evaluating the efficacy of anti-reflux medications in COPD did not report on the impact of these pharmacologic therapies on lung function [ 12 , 32 , 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significant decline in lung function with PPI and/or H 2 blocker use in this cohort is also likely due to confounding-by-indication. Xiong et al suggested that treatment of GERD with PPI in patients with COPD is associated with delayed deterioration of FEV 1 after 1-year follow-up [ 43 ]. However, several other studies evaluating the efficacy of anti-reflux medications in COPD did not report on the impact of these pharmacologic therapies on lung function [ 12 , 32 , 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPIs are mainly prescribed for GERD and the association between GERD and lung diseases has been established although the mechanism of action and causality have not. Accordingly, there has been an interest in the effect of PPI on chronic lung diseases and although results are controversial (Laheij et al, 2004; Filion et al, 2014; Benson et al, 2015; Lee et al, 2015; Othman et al, 2016), PPIs appear to have anti-inflammatory properties in COPD and IPF (Ghebremariam et al, 2015; Xiong et al, 2016). One of the hallmarks of the lung pathophysiology in CF is the chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…290 Oral lansoprazole has been effective in preventing exacerbations by inhibiting gastric secretion, reducing reflux, and decreasing levels of inflammatory markers in sputum. 291…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 99%